Pac Early Child Educ Res Assoc 2017
DOI: 10.17206/apjrece.2017.11.3.81
|View full text |Cite
|
Sign up to set email alerts
|

How Do Children Learn? Beliefs and Practices Reported by Kindergarten Teachers in Singapore

Abstract: This study explored the curriculum-related beliefs and practices reported by Singapore kindergarten teachers at a time when concerted efforts are being made to promote children's holistic development through a child-centered curriculum that emphasizes active learning through play and interaction. A questionnaire was administered to a sample of 167 teachers of 4-to 5-year-olds. Factor analyses revealed three reliable factors for teachers' beliefs and four factors for their classroom practices.Teachers endorsed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Based on the findings from Tan and Rao (2017), the Singapore government strongly encourages and provides allocations for new kindergarten teachers to undergo training to improve their skills, knowledge, and qualifications. As a result, since 2006, kindergarten teachers in Singapore had at least Diploma level and have attended courses and training related to the curriculum to strengthen classroom TnL.…”
Section: Issue Of Lack Of Training In the Implementation Of National ...mentioning
confidence: 99%
“…Based on the findings from Tan and Rao (2017), the Singapore government strongly encourages and provides allocations for new kindergarten teachers to undergo training to improve their skills, knowledge, and qualifications. As a result, since 2006, kindergarten teachers in Singapore had at least Diploma level and have attended courses and training related to the curriculum to strengthen classroom TnL.…”
Section: Issue Of Lack Of Training In the Implementation Of National ...mentioning
confidence: 99%
“…Tang (2015) found that the participating teachers strongly believed in the value of using developmentally appropriate materials and the child-centered pedagogy, reflecting a paradigm shift of the national early education toward a less academic-focused, teacher-led, but more child-centered curriculum. In a survey study, Tan and Rao (2017) reported that teachers believed in both child-centered and teacher-centered pedagogies, but they have a stronger recognition of the child-centered approach. Consistently, Ebbeck et al (2019) found that 91% of teachers valued outdoor play as it could support children's physical and social-emotional development.…”
Section: Perceived Curriculummentioning
confidence: 99%
“…In general, individual nations have varied somewhat in what they consider appropriate/inappropriate practices (e.g., Kim 2008, Kim et al 2005, and McMullen et al 2005. Research studies conducted in countries that include China, Ecuador, England, Finland, Greece, Hungary, India, Jordan, South Korea, Taiwan, Singapore, and Turkey elucidate worldwide perspectives regarding teachers' beliefs toward DAP and have shown relationships between varied sociocultural aspects and educational systems in different nations and how teachers and educators may view DAP (Erdiller Akin and McMullen 2003;Hoot et al 1996;Hedge and Cassidy 2009;Hsieh 2004;Lin 2004;Liu 2007;Ting Tan and Rao 2017). Concomitant with the need to expand DAP research worldwide, a few studies have been conducted in the Middle East, particularly in Jordan (e.g., Abu-Jaber et al 2010, Haroun and Weshah 2009, and Rababah 2012, Lebanon (Faour 2003), and Oman (Mohamed and Al-Qaryouti 2016).…”
mentioning
confidence: 99%